Higher education at the Institut Hospitalo-Universitaire Méditerranée Infection. (November 2018) - La Scola, B.; Fournier, P.-E.; Mege, J.-L.; Colson, P.
Abstract: Since its creation in 2011, the Institut Hospitalo-Universitaire Méditerranée Infection (IHU MI) has devoted a major part of its funding to support higher education programs. In 2017, on a recurrent budget of 5.8 million Euros per year, 2.9 (50%) were spent on infrastructure, mostly for maintenance and equipment of our new building. Among the remaining 2.9 million Euros, 2.3 (80%) have been dedicated to support higher education programs.